Handwritten character recognition using neural network - Hussain, Shoumin Rafsun; Nelema, Mahima Noor; Kabir, Fahim M; Patwary, Mohammad Rasheduzzaman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.